2005
DOI: 10.3152/147154605781765463
|View full text |Cite
|
Sign up to set email alerts
|

Impact mitigation in environmental impact assessment: paper promises or the basis of consent conditions?

Abstract: This study analysed 40 planning applications in the East of England to investigate the practice of translating paper recommendations in the environmental statement (ES) into legal conditions and obligations. A high proportion (50%) of suggested mitigation measures were not translated into planning conditions or obligations. However, a significant number of additional conditions or obligations, not directly based on the ES, were imposed on developers. The research suggests a mismatch between the practice of tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 29 publications
2
38
0
3
Order By: Relevance
“…Overall, the number of cases where uncertainties identified in the EIS were not addressed by follow-up, or by any other means, was higher than the number of cases where uncertainties were addressed. The proponent's EIS typically relied on the anticipated success of mitigation measures, on contingency plans, and on follow-up programs that were never discussed in depth with regard to uncertainties À an approach characterized by Tinker et al (2005) as 'paper promises'.…”
Section: Good and Poor Practicesmentioning
confidence: 99%
“…Overall, the number of cases where uncertainties identified in the EIS were not addressed by follow-up, or by any other means, was higher than the number of cases where uncertainties were addressed. The proponent's EIS typically relied on the anticipated success of mitigation measures, on contingency plans, and on follow-up programs that were never discussed in depth with regard to uncertainties À an approach characterized by Tinker et al (2005) as 'paper promises'.…”
Section: Good and Poor Practicesmentioning
confidence: 99%
“…they don't reflect what's actually going to happen over the next couple of years'. Previous studies have identified the frequent time lapses between the EIA and development completion as a potential limit to EIA effectiveness (Tinker et al 2005). Again this concern does not recognise the role that EMS (and indeed EIA follow-on) can play in ensuring EIA outputs are integrated with the EMS.…”
Section: Benefits and Flaws Of The Eia Processmentioning
confidence: 96%
“…Insufficient implementation of mitigation measures has been highlighted as a flaw of EIA (Sánchez & Hacking 2002), and research has found EIA to be successful in some respects (Tinker et al 2005;Jay et al 2007;Obradovic 2011;Bassi et al 2012) but has also questioned its overall effectiveness, particularly when there is no legislation requiring follow-up (Arts 1998;Nitz & Holland 2000;Gallardo & Sánchez 2004;Slinger et al 2005;Morrison-Saunders et al 2007).…”
Section: Current Issues With Eia and Emsmentioning
confidence: 99%
See 2 more Smart Citations